Questioning the existence of the prosumer in Ibero-America. A study on university students from Colombia, Peru, Chile and Spain (2018)
Contemporary media faces two serious problems: the loss of users, on the one hand, as an effect of the emergence of new spaces for social participation, such as social networks; and, on the other, a generalized loss of credibility. Given this scenario, interactivity -which is responsible for mediating the relationship between media and users- emerges as a key factor in adapting the media to the internet. With this study, and after a survey of 2986 university students from Colombia, Peru, Chile and Spain, we analyzed both the relationship between consumption and confidence in the media, as well as the aspects that this population demands from an informative website. Among the most interesting results, we observed the prevalence of greater confidence in traditional media, despite the fact that the students consulted recognize spending more time on online platforms. In addition, we found among the respondents that the processes of production and consumption appear delimited, with a pronounced inclination towards the second -consumption-, to the detriment of production. © 2018 Department of Spanish Literature of the University of Granada. All rights reserved.